3D printed self‐expandable vascular stents from biodegradable shape memory polymer - Jia, Han; Gu, Shu‐Ying; Chang, Kun (Advances in polymer technology, 2018)
Considering the high in‐stent restenosis and stent thrombosis rate of stent implantation with balloon angioplasty, self‐expandable biodegradable vascular stent was prepared by 3D printing from shape memory polylactide (PLA). The printed stent could be compressed into a temporary shape with thinner diameter easy for implantation. The compressed stent had excellent shape fixity and could maintain its temporary shape at room temperature for storage. However, it could self‐expand to its initial shape after being implanted due to the heat triggering of shape memory polylactide. The longitudinal contraction or radical expansion under its working condition was carried out by finite element analysis. The combination of self‐expansion of biodegradable shape memory PLA with personalized designing of 3D printing provides the vascular stent a future solution for cardiovascular disease treatment.